CLASSROOM COMMUNICATION SKILLS: THE NEED TO FILL A GAP IN THE TRAINING OF TEACHERS OF SPANISH AS A FOREIGN LANGUAGE - Francisco J. Rodríguez Muñoz; Víctor M. Madrid Navarro (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
This paper sets out the necessity of examining the communication skills of teachers of Spanish as a foreign language as conducted in other socio-educative contexts. According to this objective, the paper begins with a review of theoretical efforts that have been made during recent years referring to research methodology (such as instruments), and to their main results. This leads to a discussion of the training needs that teachers of Spanish as a foreign language presently face for the development of their communication skills in the classroom and, in general terms, the paper discusses the different types of ideas and strategies that must be considered during teachers' instruction. Finally, this brief proposal expects to be the seed of future research projects that impact positively on the improvement of teachers' communication competence, whereby the ideas discussed here are taken as a nuclear component in the frame of future teaching competence.